Effect of trained evacuation leaders on victims' safety during an active shooter incident. (February 2023) - Arteaga, Cristian; Park, JeeWoong; Morris, Brendan Tran; Sharma, Sharad
Highlights: Agent-based simulation for leadership effect in active shooter incidents. The social forces model of pedestrian dynamics to accurately describe crowd motion in escape. The leadership effect was investigated with behavioral parameters of leaders, victims, and shooter. Analysis reveals several intriguing findings in relations to the studied parameters. Even few leaders' presence may provide substantial benefits for victim's safety. Abstract: Trained evacuation leaders in emergency offer the potential for improved decision making and evacuation. Compared to victims, trained evacuation leaders can make educated assessments of the situation based on their training, knowledge of the facilities, and additional details about the incident, which enables them to guide victims in choosing a safe departure time and evacuation route. Despite a general understanding about the benefits of such leaders in evacuation, mass shooting cases require a separate attention because these cases are more complex with different behavioral decisions, not just running away, with a continuously changing source of the hazard source, the shooter. This study develops a simulation model package and evaluates the effect of trained evaluation leaders on the victim safety during an active shooter incident. The study leverages sophisticated human motion dynamics models and human behaviors supported by past literature in an agent-based model. The study varies several parameters (e.g., occupancy, firing rates and gun range, and victims' decision of running or hiding) in this simulation to draw generalized conclusions on the leaders' impact on various scenarios. The results reveal general findings with several interesting points. Overall, increased leaders' presence contributes to fewer fatalities. Even few trained leaders, compared with none, can considerably improve victim safety. Even if leaders are not uniformly positioned, they still provide substantial benefits for victim's safety. The leaders' benefits were consistently found in various parametric studies (e.g., number of leaders, occupancy, leaders' strategic placement, gun range, and shooting rate) that support the mentioned findings.